Efficiency of slow sand filter in purifying of tube well water in Kg. Fajar, Gambang, Kuantan - Nurul Masliana, Khairil Anuar (2015)
Slow Sand Filter (SSF) can be effective for water purification. The purpose of purifying water is to increase the quality of water that is harmless and safe for human consumption. The formation of “schmutzdecke” can vary the efficiency of SSF. The tube well in the water distribution system in the study area. The untreated water from tube well was collected from Kg. Fajar, Gambang. Unfortunately, the main problem of tube the well water is the contamination by E. coli and heavy metal. Therefore, required filtration has been analyzed to increase the water quality and efficiency to remove of E. coli and reduce selected parameters. To solve this problem SSF with adding coconut fibers, bagasse and oil palm fibers were recommended to treat the tube well water. The guideline values of water quality was based on National Drinking Water Quality Standard Malaysia (NDWQS). The percentage removal of heavy metal in water were also analyzed perfectly. SSF with adding coconut fibers, bagasse and oil palm fibers has been shown to be effective for the removal of E. coli and reducing selected parameters. From the study results, the removal of physical parameters was up to 93%, while for chemical parameters up to 73%. Hence, SSF can be used for removal of E. coli and heavy metal in the study area